Hubungan Hipertensi dengan Klasifikasi Hernia Nukleus Pulposus Lumbal berdasarkan Magnetic Resonance Imaging - Sunjata, Winda Putri; Meutia, Yurida Binta; Sukmaningtyas, Hermina; Pudjonarko, Dwi (RSUP Dr. Kariadi, 2021)
ABSTRACT BACKGROUND : Hypertension is a disease that is known to affect other diseases. Recent research finds that HT is associated with disc degeneration disease. Herniated nucleus pulposus (HNP) lumbar as a result from disc degeneration disease need to be known to be affected by hypertension or not. OBJECTIVE: To know the relationship between hypertension and the classification of disc degeneration based on Pfirrmann’s criteria and herniated nucleus pulposus lumbar classification based on magnetic resonance imaging. METHOD : This research use descriptive observational with cross sectional design. Subjects were 62 lumbar HNP patients diagnosed at RSUP Dr. Kariadi Semarang from January 2019 - March 2020. The subject data were analyzed using non-parametric Chi Square test and Mantel Haenszel test. RESULT : Based on the analysis, it was found that p>0.05 was found in the relationship between age and sex with the classification of disc degeneration and lumbar HNP. The result of correlation test between hypertension and disc degeneration classification is p<0,05 with odds ratio 14,700 and lumbar HNP classification is p >0.05. In relation to the classification of disc degeneration with lumbar HNP classification, the value of p >0.05 was also obtained. CONCLUSION : There was no association between age, sex, the classification of disc degeneration and lumbar HNP classification. There was a significant association between hypertension and the classification of disc degeneration with the individual risk of hypertension increasing 14,7 times but no association was found with lumbar HNP classification. Keywords: Disc degeneration; Hypertension; Lumbar herniated nucleus pulposus